2016
DOI: 10.4143/crt.2015.475
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Axillary Nodal Ratio after Neoadjuvant Chemotherapy of Doxorubicin/Cyclophosphamide Followed by Docetaxel in Breast Cancer: A Multicenter Retrospective Cohort Study

Abstract: PurposeThe purpose of this study is to investigate the prognostic value of lymph node (LN) ratio (LNR) in patients with breast cancer after neoadjuvant chemotherapy.Materials and MethodsThis retrospective analysis is based on the data of 814 patientswith stage II/III breast cancer treated with four cycles of doxorubicin/cyclophosphamide followed by four cycles of docetaxel before surgery. We evaluated the clinical significance of LNR (3 categories: low 0-0.20 vs. intermediate 0.21-0.65 vs. high 0.66-1.00) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Lim et al [18] reported analyzed the data from 7,856 Korean women and reported that lower-inner quadrant tumors showed poor prognoses only in case of HER2 overexpression and triple-negative breast cancer. Some researchers have reported the prognostic value of nodal ratio after NAC, and have shown that this prognostic value is significant in certain molecular subtypes; however, the results are inconsistent [1920]. In the present study, we found that luminal A subtype breast cancer and a low nodal ratio conferred an OS advantage over the others; however, we could not identify any relationship between the molecular subtype and tumor location as well as nodal ratio.…”
Section: Discussioncontrasting
confidence: 81%
“…Lim et al [18] reported analyzed the data from 7,856 Korean women and reported that lower-inner quadrant tumors showed poor prognoses only in case of HER2 overexpression and triple-negative breast cancer. Some researchers have reported the prognostic value of nodal ratio after NAC, and have shown that this prognostic value is significant in certain molecular subtypes; however, the results are inconsistent [1920]. In the present study, we found that luminal A subtype breast cancer and a low nodal ratio conferred an OS advantage over the others; however, we could not identify any relationship between the molecular subtype and tumor location as well as nodal ratio.…”
Section: Discussioncontrasting
confidence: 81%
“…CE(A)F regimen chemotherapy has been the mainstay of NCT therapy for BC patients, however, the majority of patients will develop resistant, and ultimately recurrence [ 23 , 24 ]. It is our hope that this study will add to the body of literature for prediction the PI3K/PTEN/AKT pathway genetic polymorphisms lead to individual variation in response to CE(A)F regimen and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostics of breast cancer patients after preoperative therapy had been discussed in several studies. [ 17 , 19 , 23 , 28 ] However, factors that independently and optimally reflect breast cancer patients’ survival who received PRT followed by MAST were still scarcely discussed. In the current study, we evaluated 1350 NMBC patients who received MAST after PRT and first developed a novel T-NR staging system.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 , 22 ] However, whether the mLNR was a better indicator than pN staging for breast cancer patients after preoperative therapy was still controversial. In 2016, Kim et al [ 23 ] conducted a multicenter retrospective study, and eventually they demonstrated that mLNR was not superior to pN staging in predicting clinical outcome of breast cancer after preoperative therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation